The behaviour of the power transmission tower subjected to horizontal support's movements. (15th September 2016) - Shu, Qianjin; Yuan, Guanglin; Huang, Zhaohui; Ye, Sheng
Highlights: Design a scaled test tower model for a typical 110 kV power transmission tower. Conduct two tests on the scaled test tower model under the support's movements. Develop a FE model using ANSYS for modelling the 110 kV power transmission tower. Abstract: In this paper, two half-scaled test tower models for a typical 110 kV single-circuit power transmission tower were designed and fabricated. The scaled test tower models were tested under the horizontal support's stretching (tensile) and compressive movements with the normal working loading conditions. The deformations of the tested tower models and stresses within the different bracing members were fully measured. A large amount of comprehensive test data was generated. Also a finite element (FE) model using the software ANSYS was developed and validated by the test data. The research indicated that the designed half-scaled test tower model can reasonably represent the behaviour of the whole transmission tower under the horizontal support's movements. The magnitude of the stresses was reduced from the bracing members at lower part to the bracing members at higher part of the tower. The effect of the ground surface deformations is more significant on the truss members closed to the supports. Hence, for the design of transmission tower against the horizontal support's movements, it is important to reduce the slenderness of those bracing members.